Histopathological Changes Caused by Monochromatic Wavelengths in the Retina of Two Species of frogs - Baker, Semaa Ahmed; Abd, Ali Ashgar (International Journal of Scientific Research in Biological Sciences, 2022)
The current research deals with the study of the effect of monochromatic visible radiation on the retina of the eye, which are a beam of blue light whose wavelength ranges from 450-500 nanometers and intensity of illumination of 200 lux and under a temperature of 10oC in winter and 20? in summer, and a beam of yellow light whose wavelength ranges from From 550-600 nanometers, with an intensity of 225 lux, and under the same temperatures, for three months for each of the two lights. I took two types of frogs, the first is the swamp frog Rana ridibunda ridibunda and the second tree frog Hyla arborea savignyi. The effects in type 1 retina were generally greater than in type 2. On the other hand, the effects of blue light were more than yellow light in general, with close damage to the two lights in some cases, and the damage was at a high temperature of 20? more than at the temperature of 10? for the two types of light. The damage caused by monochromatic colors of visible light appeared to follow the wavelength, temperature, and intensity of illumination, as the shorter the wavelength, the higher the temperature and the higher the intensity of the illumination, the greater the damage to the components of the eye, and the absence of clots in the tissue of the eye indicates that the light damage occurred by the mechanism photochemical.